Efficiency in academic evaluation: data envelopment analysis systematic review - Razi, Nor Faezah Mohamad; Baharun, Norhayati; Masrom, Suraya (International Journal of Evaluation and Research in Education (IJERE), 2024)
Education 5.0@UiTM is transforming Universiti Teknologi MARA (UiTM). This new approach emphasizes flexible learning paths that teach life and cross-disciplinary skills. To make higher education future-ready, universities must adapt fast to the significant global and technical changes caused by the 4th Industrial Revolution and transition from content-based to individualized learning. To ensure students meet Education 5.0@UiTM standards and corporate needs, the evaluation process must be reviewed. Competency-based academic achievement evaluation outperforms grades. This assessment is rarely systematically analyzed. This study was conducted to thoroughly explore the selection of input and output factors in determining student achievement efficiency using the data envelopment analysis (DEA) approach. The study reviewed publications from Scopus, Google Scholar, and Science Direct and found six themes for input variables: human resources, facilities condition and equipment, finance, curriculum, students characteristics, and community resources. output variables included student achievement, satisfaction, graduation rate, employment, research, and community resources. In DEA analysis, input and output selection affects scope, aim, production frontier, efficiency scores, accuracy and completeness. So, characterizing student achievement requires choosing relevant input and output variables. This study can enhance student evaluation processes to prepare college graduates for the next industrial revolution.